Strengthening Madrasah Administrative Governance Through Cloud Storage and Notion-Based Collaborative Workspace: A Digital Transformation Initiative for Madrasah Aliyah - Fari Katul Fikriah; Amelia Devi Putri Ariyanto (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to design and implement a cloud storage–based administrative management model integrated with a collaborative workspace using Notion for madrasahs affiliated with the Semarang City Private Madrasah Family Association (PKMAS). The program adopted a participatory approach consisting of needs assessment, model development, implementation through training and mentoring, evaluation, and monitoring to ensure the achievement of program objectives. The program resulted in an integrated, practical, and readily adoptable digital administrative management model for madrasahs. In addition, it enhanced the digital competencies of educational staff and promoted more collaborative administrative work practices. The implementation of the program led to improvements in participants' knowledge, digital skills, and administrative management efficiency. Evaluation results demonstrated increased participant competence following the training, with the mean understanding score increasing from 2 to 5 in digital administration, cloud storage utilization, and collaborative work, and from 0 to 4 in the use of Notion. Furthermore, 93.9% of participants reported satisfaction with the program. The program was implemented across 13 PKMAS-affiliated madrasahs and involved 33 participants, demonstrating its potential to support more integrated, efficient, and collaborative administrative management.